2017
DOI: 10.1186/s12955-017-0764-z
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life improvement after a three-year course of sublingual immunotherapy in patients with house dust mite and grass pollen induced allergic rhinitis: results from real-life

Abstract: BackgroundAlong with its high prevalence, the burden of allergic rhinitis rests upon the serious impact on quality of life of patients. Allergic rhinitis is associated with impairments in daily activities, work and school performance, and practical problems. Patients suffer from sleep disorders and emotional problems. Тhe advantages of sublingual immunotherapy on quality of life have only recently begun to emerge. The objective of this prospective real-life study was to evaluate the effect of a three-year cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 27 publications
2
27
0
2
Order By: Relevance
“…Several validated tools for assessing HRQoL in AR are currently available (30). The most frequently used specific and validated instrument, involved in AIT trials is the RQLQ questionnaire (23,26,27). Moreover, only the RQLQ allows calculating the MID, namely how much a score must change so that it is perceived as such by the patient, irrespective of its statistical significance (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several validated tools for assessing HRQoL in AR are currently available (30). The most frequently used specific and validated instrument, involved in AIT trials is the RQLQ questionnaire (23,26,27). Moreover, only the RQLQ allows calculating the MID, namely how much a score must change so that it is perceived as such by the patient, irrespective of its statistical significance (31).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a number of studies with AIT have been reported, where the improvement in HRQoL is evaluated mostly as a secondary efficacy variable (19,20,21,22). These studies had shown positive results in HRQoL, but most are clinical trials with sublingual immunotherapy (SLIT), and data from real life studies are still scarce (23,24). Therefore, there is still a need for more clinical evidence, specially with non-interventional studies, where a higher representation of patient's population can be included, as children, patients with comorbidities, etc.…”
Section: List Of Abbreviationsmentioning
confidence: 99%
“…The results showed that SLIT approximately halved the symptom-medication scores compared to the score registered in drug-treated patients. Since then, several real-life studies were performed, including 11 studies on SCIT (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), 15 on SLIT (6,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and 5 on both (30-…”
Section: Real-life Studies On Aitmentioning
confidence: 99%
“…The rates of avoidance in mono-allergen, pollen-mixture and 2-simultaneous-allergen SLIT were 93.6, 83.3 and 73.7%, respectively. A significantly higher avoidance (p = 0.0001) was observed in children with longer-duration SLIT (28). Another aspect evaluated in a single study was the ability to prevent the development of asthma in subjects treated for AR.…”
Section: Other Issues Investigatedmentioning
confidence: 99%
“…The available data indicate that AR and asthma markedly affect the physical, emotional and social dimensions of patients' experience [7,8]. This is supported by evi-dence that successful treatment of respiratory allergy improves the HRQoL [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%